Full Outline of Unresponsiveness Score and Brainstem Sign Score Application to Predict Mortality of Patients with Severe Head Injuries at Gambiran Public Hospital of Kediri - Christina Dewi Prasetyowati (STIKes Patria Husada Blitar, 2020)
There are many factors and variables that influence the prognosis in patients with severe head injuries make determining the prognosis for patients with severe head injuries become difficult. There are two parameters that can predict the prognosis of severe head injury patients with optimal full outline of unresponsiveness score (FOUR score) and brainstem sign score (BSS). FOUR scores can provide a wealth of information about the scale of neurological signs that are quick and easy used for unconcious patients. BSS is an assessment to predict the death of a person permanently to determine whether there is a physiological function that is not function normally. The aimed of this study was to determine ratio of FOUR score and BSS in determining the prognosis of patients with severe head injury at RSUD Gambiran Kediri. The type of study was cross sectional approach. The sampling technique used consecutive sampling technique and obtained a sample of 60 people. The data was analyzed by using chi-square test for comparison of FOUR score and BSS in determining the prognosis of severe head injury patient at RSUD Gambiran Kediri. Based on the results of study by chi-square test showed that p FOUR score = p BSS = 0,004, which meant the FOUR score and BSS was determined the prognosis of patients with severe traumatic head injury at RSUD Gambiran Kediri. The study showed that there was no difference between the FOUR score and BSS in determining the prognosis of severe head injury patient at RSUD Gambiran Kediri but FOUR score could be used in incubated or ventilated patients. Based on the results of this study, it is advisable to use scoring method more easily and according to the condition of the patient is with the installed ventilator or non ventilator.